Defects in β-cell Ca2+ dynamics in age-induced diabetes - Li, Luosheng (2015)
Little is known about the molecular mechanisms underlying age-dependent deterioration in β-cell function. We now demonstrate that age-dependent impairment in insulin release, and thereby glucose homeostasis, is associated with subtle changes in Ca2+ dynamics in mouse β-cells. We show that these changes are likely to be accounted for by impaired mitochondrial function and to involve phospholipase C/inositol 1,4,5-trisphosphate–mediated Ca2+ mobilization from intracellular stores as well as decreased β-cell Ca2+ influx over the plasma membrane. We use three mouse models, namely, a premature aging phenotype, a mature aging phenotype, and an aging-resistant phenotype. Premature aging is studied in a genetically modified mouse model with an age-dependent accumulation of mitochondrial DNA mutations. Mature aging is studied in the C57BL/6 mouse, whereas the 129 mouse represents a model that is more resistant to age-induced deterioration. Our data suggest that aging is associated with a progressive decline in β-cell mitochondrial function that negatively impacts on the fine tuning of Ca2+ dynamics. This is conceptually important since it emphasizes that even relatively modest changes in β-cell signal transduction over time lead to compromised insulin release and a diabetic phenotype.